Pengaruh PDRB, IPM dan Kapasitas Fiskal terhadap Tingkat Kemiskinan di Indonesia: Studi Kasus 34 Provinsi di Indonesia Tahun 2015-2019 - Difa Faadila Kusuma; Deden Dinar Iskandar (Diponegoro Journal of Economics, 2022)
Poverty is a problem that occurs across the world, even in developed countries, especially in Indonesia. The increase in the poverty rate from year to year is a problem that must be faced by the community and the government. This study aims to analyze whether the independent variables consisting of GRDP, Fiscal Capacity, and HDI have an influence on the poverty rate in 34 provinces in Indonesia in 2015-2019. The data used in this study is panel data with time series data for the 2015-2019 period and a cross-section of 34 provinces in Indonesia. The analytical tool used is panel data regression analysis using the Eviews10 program. From the stages of analysis carried out, the results of data analysis showed that the results of the panel data estimation selected the best model, namely the Random Effect Model (REM). The results showed that the GRDP variable had a positive and significant effect on poverty, while the variables of Fiscal Capacity, and HDI have a negative and significant effect on the poverty level.